Inverse dynamic analysis of milling machining robot, application in calibration of cutting force - Hai, Ha Thanh (Vietnam Journal of Science and Technology, 2019)
This article presents analysis of inverse dynamics of serial manipulators in milling process. Cutting forces and complicated motion involve to difficulties in solving dynamics problems of robots. In general, cutting forces are determined by using empirical formulas that lead to errors of cutting force values. Moreover, the cutting forces are changing and causing vibration during machining process. Errors of cutting force values affect to the accuracy of the dynamic model. This paper proposes an algorithm to compute the cutting forces based on the feedback values of the robot's motion.